The Relationship Between Influencer Marketing and Generation Z Purchase Intention - Nuriyati Samatan; Ariandi Putra; Intania Intania (Green Publisher, 2026)
This study aims to analyze Influencer Marketing as variable X and Purchase Intention as variable Y. The object of this study is Generation Z's appreciation of Sombong Men's Care skincare products in Jakarta. The theory applied is the S-O-R. This study employs a quantitative approach within the positivism paradigm. A non-probability, purposive sampling method was utilized, with the sample size calculated using Slovin's Formula at a 10% margin of error. Data were collected via an online questionnaire distributed to 100 Generation Z respondents living in Jakarta who had been exposed to promotional content for Sombong Men's Care skincare products. Data analysis was conducted using validity and reliability tests, simple linear regression, and hypothesis testing via SPSS software. The hypothesis testing results revealed that the calculated t-value exceeded the table t-value (20,231 > 1,660). Consequently, the null hypothesis is rejected and the alternative hypothesis is accepted, indicating a significant effect of influencer marketing on purchase intention. The coefficient of determination demonstrates an effect contribution of 0.807 or 80.7%, while the remaining 19.3% is influenced by other factors. The findings demonstrate that influencer marketing has a significant impact and a strong relationship with consumer purchase intention.